2013
DOI: 10.1186/1471-244x-13-287
|View full text |Cite
|
Sign up to set email alerts
|

A multi-centre cohort study of short term outcomes of hospital treatment for anorexia nervosa in the UK

Abstract: BackgroundIndividual, family and service level characteristics and outcomes are described for adult and adolescent patients receiving specialist inpatient or day patient treatment for anorexia nervosa (AN). Potential predictors of treatment outcome are explored.MethodAdmission and discharge data were collected from patients admitted at 14 UK hospital treatment units for AN over a period of three years (adult units N = 12; adolescent N = 2) (patients N = 177).ResultsOne hundred and seventy-seven patients with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 47 publications
7
88
0
1
Order By: Relevance
“…Research demonstrates that outcomes of, and satisfaction with inpatient treatment for AN are variable [25] with minority of patients finding treatment 'extremely helpful' [7]. While weight may be restored, psychological symptoms remain and repeated readmission is common [7,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Research demonstrates that outcomes of, and satisfaction with inpatient treatment for AN are variable [25] with minority of patients finding treatment 'extremely helpful' [7]. While weight may be restored, psychological symptoms remain and repeated readmission is common [7,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…A recent multicentre cohort study of short-term outcomes of hospital treatment of AN in the UK found a mean admission BMI of 14 kg/m 2 , a mean discharge BMI of 17.3 kg/m 2 and a mean illness duration of 8 years for adults. 219 This suggests that our case mix was very similar to that of a typical adult inpatient with AN.…”
Section: Discussionmentioning
confidence: 68%
“…Furthermore, the average length of stay reported in HES is much lower than that reported by a recent 384 which reported a length of stay of over 18 weeks, and a recent study on the duration of stay in UK specialist ED units reported an average length of stay of 26 weeks for adults and of 29 weeks for adolescents. 219 One possible explanation is that HES conflates stays in psychiatric or ED units (typically for weight restoration or other mental health concerns such as self-harm) and stays in medical or paediatric units often linked to acute medical issues, which tend to be much shorter. In addition, HES data may not be entirely reliable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the proportion of patients with poor responses in recent naturalistic studies appears to be critically high: more than half of the patients remain underweight (BMI <17.5) at discharge [1,2], and there is a strong need for more effective treatments for inpatients with AN [3]. …”
Section: Tablementioning
confidence: 99%